Appetite regulations after sprint exercise under hypoxic condition in female athletes - Kojima, C.; Kasai, N.; Ishibashi, A.; Murakami, Y.; Ebi, K.; Goto, K. (The Journal of Strength and Conditioning Research, 2019)
The present study determined changes in appetite-regulating hormones and energy intake after high-intensity interval exercise (HIIT) under hypoxic conditions (HYP) in trained female athletes. Fifteen female athletes completed 3 trials on different days of either HIIT under HYP, HIIT under normoxic conditions (NOR), or rest in normoxia (CON). Exercise trials consisted of 2 successive sets of 8 repeated bouts of a 6-second maximal sprint separated by a 30-second rest. Blood samples were obtained to measure plasma acylated ghrelin, glucagon-like peptide-1 (GLP-1), and metabolite concentrations. Energy intake during an ad libitum buffet meal test was evaluated 30 minutes after exercise or rest. Plasma acylated ghrelin concentrations decreased significantly after exercise (p = 0.001), but no difference was observed between the HYP and NOR. Plasma GLP-1 concentrations did not differ after exercise, with no difference between the HYP and NOR. Although absolute energy intake in the HYP (634 ± 67 kcal) and NOR (597 ± 63 kcal) was significantly lower than that in the CON (756 ± 63 kcal, p = 0.006), no difference was observed between the HYP and NOR. These results show that HIIT under hypoxic and NOR lowered plasma acylated ghrelin concentrations and energy intake.